Construção do conhecimento científico nos Programas de Pós-Graduação stricto sensu em Ciências Contábeis sob a ótica das redes sociais - Joao Estevao Barbosa Neto (2011)
The scientific field of accounting has had a significant development in recent years. This evolution is built on a social structure in which the relationship among researchers and research practices is reflected on the construction of scientific knowledge. Based on this premise, this study aimed to identify and analyze the dynamics of relationships structure among the programs of stricto sensu post-graduate studies in Brazilian Accounting area under a social networks perspective. Thus, it was a descriptive study, using the Social Network Analysis to identify thenetwork structure of scientific and academic collaboration among teachers of stricto sensu postgraduate studies programs in Accounting. The relational structure was identified through teachers collaboration in co-authorship of scientific articles published in journals and participation in boards of M.Sc (Masters Degree) and PhD (Philosophy Doctor) in Accounting. Thus, by collecting data on programs from websites and in the curricula of Lattes platform for teachers, two hundred and forty-one teachers were identified from eighteen stricto sensu post-graduate studies programs on Accounting who collaborated with each other in four hundred and fifty-five articles, one thousand and two Masters stalls and one hundred and two doctoral stalls from 2002 to 2010 (divided into three periods, 2002-2004, 2005-2007, and 2008-2010) The hypothesis about the collaboration network among stricto sensu post-graduate studies programs on Accounting providing structures such as Small Worlds was also tested. Results analysis was divided into two parts. Initially, we tried to draw a demographic profile of accounting scientific field through adescriptive analysis of academic and scientific characteristics from programs and teachers. The second part was to analyze the relational structure among teachers based on Social Network Analysis. Results showed an evolution on accounting area profile, both in number of programs and in number of new teachers. The field incipient nature shows a relevant variety of teachers with training in other knowledge areas, especially when considering masters and doctoral levels.It was verified that teachers had relevant increase on scientific and academic activities, specifically with articles publication in journals, books edition, and participation in master's and doctoral stalls. As for Social Network Analysis, even analyzed separately, results showed similar relational structures in three types of interaction. Therefore, the longitudinal analysis showed significant progress during the analyzed period, verifying the great growth of the network, both in terms of number of participants and in the relationships among them, contributing to thedecreased network density and become more dispersed. It was found that the creation of new programs for stricto sensu post-graduate studies on Accounting was crucial for enhancing collaboration on articles and on newsstands of master's and doctoral degrees, causing to grow alsothe interaction among the programs. It was also found that the insertion of new teachers in the program significantly influenced the relational structure, contributing to the field evolution. The research hypothesis about the collaboration network among programs in stricto sensu postgraduate studies on Accounting providing structures such as Small Worlds was accepted as regards the collaboration and participation on articles and on newsstands for a doctorate, but was rejected in the interaction at masters newsstands. Faced with such evidences, results identified an accounting field profile, indicating a future scenario for the evolution of scientific and academic collaboration, confirming that scientific knowledge is created and developed from the social relations of the actors involved in the area.